Bearing the Weight of Imprisonment: The Relationship Between Prison Climate and Well-Being - Ginneken, Esther F. J. C. van (Criminal justice and behavior, 2019)
Little is known about the relative influence of shared and individual perceptions of prison climate on adjustment to incarceration. This study investigated the relationship between prison climate and well-being among a sample of 4,538 adults incarcerated in the Netherlands. Prison climate dimensions were considered both as prison unit-level variables and as individual-level perceptions. Multilevel analysis results showed that most variance for well-being is found at the individual rather than the unit level. This implies that it does not make much of a difference for well-being in which prison unit someone resides. Positive effects of prison climate on well-being were primarily found for individual perceptions of prison climate, rather than for the aggregate unit measures. More research is needed to determine whether this finding holds true in other countries. The findings confirm the importance of disentangling the contribution of prison climate at the individual and group level.